Comparison of neurodevelopmental outcomes between monochorionic and dichorionic twins with birth weight ≤ 1500 g in Japan: a register-based cohort study. (October 2018) - Ichinomiya, Kenji; Maruyama, Kenichi; Koizumi, Aya; Inoue, Fumitaka; Fukuda, Kazuyo; Kaburagi, Kota; Miyakawa, Yoichi
Abstract Objective To examine the relationship between chorionicity and neurodevelopmental outcomes in very low birth weight twins at 3 years of age. Study design A retrospective cohort study of 3538 twins who were admitted to 91 tertiary perinatal centers in the Neonatal Research Network of Japan between 2003 and 2012. Results In a comparison of the followed-up 796 monochorionic twins and 786 dichorionic twins, the overall rate of neurodevelopmental impairment was higher in monochorionic twins; specifically, the rate of disability in the language-social area of the Japanese standardized developmental test was higher in monochorionic twins than in dichorionic twins (adjusted odds ratio, 1.55; 95% confidence interval, 1.07–2.25;P  = 0.02). Conclusions Chorionicity was associated with neurodevelopmental outcome (especially for language and social development) in a large cohort of very low birth weight twins who had a high rate of perinatal morbidity and neurodevelopmental impairment.